Nonisothermal and isothermal crystallization behavior of isotactic polypropylene/chemically reduced graphene nanocomposites. (5th January 2016) - Tang, Dahang; Li, Songrong; Yang, Junlong; Su, Juqiao; Yang, Qi; Kong, Miqiu; Huang, Yajiang; Liao, Xia
Abstract : Graphene oxide was firstly prepared by a modified Hummers method and then reduced via hydrazine reduction method to obtain chemically reduced graphene (CRG). The morphology of CRG dispersed in the isotactic polypropylene (iPP) matrix was observed using transmission electron microscope and rheological measurement methods. Nonisothermal and isothermal crystallization behaviors of iPP/CRG nanocomposites were investigated by differential scanning calorimetry and polarizing optical microscopy methods, respectively. Nonisothermal crystallization measurement revealed that CRG elevated the crystallization temperature of iPP due to the nucleating effect of CRG. And during isothermal crystallization process, the half time crystallization of nanocomposites was significantly reduced. Furthermore, the images of polarized optical microscopy also exhibited that the nucleation density of nanocomposites was much higher than that of neat iPP due to the heterogeneous nucleation of CRG even at a loading of 0.5%. POLYM. COMPOS., 38:E342–E350, 2017. © 2016 Society of Plastics Engineers